Analisis Faktor-Faktor Penghambat Penyelesaian Studi Mahasiswa Program Studi Matematika Universitas Sulawesi Barat Menggunakan PLS-SEM - Rahmah Abubakar; Muh. Rifandi; Rahmawati Rahmawati; Fatimah Fatimah (Department of Mathematics, Universitas Negeri Gorontalo, 2023)
This research aims to examine the factors that influence the completion of students' studies at the University of West Sulawesi Mathematics Study Program. The high frequency of alumni with a length of study above the expected time is a polemic that needs to be solved and followed up. The research method analyses the partial least squares structural equation model (PLS-SEM). This study involved 2016, 2017 and 2018, batch students. Data collection used an online questionnaire. The results showed that the self-control factor and the intelligence and interest factor had a significant effect on students' motivation to complete their study on time. On the other hand, environmental factors and campus instrument factors do not have a significant effect.